2018
DOI: 10.1002/cssc.201702354
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Organic–Inorganic Anatase as a Bifunctional Catalyst for Enhanced Production of 5‐Hydroxymethylfurfural from Glucose in Water

Abstract: Hybrid organic-inorganic anatase (hybrid-TiO ) is prepared by a facile hydrothermal synthesis method employing citric acid. The synthetic approach results in a high surface-area nanocrystalline anatase polymorph of TiO . The uncalcined hybrid-TiO is directly studied as a catalyst for the conversion of glucose into 5-hydroxymethylfurfural (HMF). In the presence of the hybrid-TiO , HMF yields up to 45 % at glucose conversions up to 75 % were achieved in water at 130 °C in a monophasic batch reactor. As identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The present study demonstrated that HNbWO 6 nanosheet aggregates exhibited the highest HMF yield with the highest selectivity under the lowest reaction temperature among oxides without any modifications (entries 1,2). Recent studies showed that a hybrid TiO 2 (entry 13) [34] and mesoporous metal phosphates (entries 15,16) [35,36] gave higher HMF yield as well as H 3 PO 4 -treated niobic acid (entry 14) [30]. This suggests that some modification of oxide catalysts including treatment with phosphoric acid will improve the activity.…”
Section: Resultsmentioning
confidence: 99%
“…The present study demonstrated that HNbWO 6 nanosheet aggregates exhibited the highest HMF yield with the highest selectivity under the lowest reaction temperature among oxides without any modifications (entries 1,2). Recent studies showed that a hybrid TiO 2 (entry 13) [34] and mesoporous metal phosphates (entries 15,16) [35,36] gave higher HMF yield as well as H 3 PO 4 -treated niobic acid (entry 14) [30]. This suggests that some modification of oxide catalysts including treatment with phosphoric acid will improve the activity.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction temperature basically ranged in 120-200 C, althought the temperature below 140 C typically gave relatively low HMF yield. 26,38,39 The HMF yield above 50% were obtained from catalysts functionalized by acids including SO 3 H-ZSM-5, 69 SnP, 70 PO 4 /NU(half), 15 and Fe/AR. 67 The SO 3 H-SPPS catalyst exhibited very high HMF yield of 87% in an ionic liquid [EMIM]Cl as a reaction medium, yet the cost effectiveness of ionic liquid remains controversial in an industrialization aspect.…”
Section: Effects Of Reaction Setupmentioning
confidence: 99%
“…38 Similarly, hybrid organic-inorganic anatase (hybrid-TiO 2 ), which is synthesized by a hydrothermal synthesis technique using citric acid (CA), displays the HMF yield of 45%. 39 Such low to moderate HMF yields are likely due to the instability of HMF in heated water leading to various side products. 34 Here, we report a catalytic system comprising a phosphate-modied TiO 2 catalyst (P-TiO 2 ) for high yield production of HMF from glucose.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of this system is threefold: i) Mixtures of cyclohexane/1,4-dioxane are representative of typical hydrocarbon and oxygenated heterocyclic compounds used as solvent media in liquid-phase catalysis. In addition, TiO2 is used in catalytic reactions as support [7,8] and catalysts [9,10]. The role of such materials in affecting adsorption and catalytic performances is often considered to be a key step [11,12].…”
Section: Introductionmentioning
confidence: 99%